Modelling and applications of conductive elements on textile materials. Issue 5 (10th August 2018) - Pawlak, Ryszard; Lebioda, Marcin; Tomczyk, Mariusz; Rymaszewski, Jacek; Korzeniewska, Ewa; Walczak, Maria
Abstract : Purpose: Passive conducting elements are the important parts of textronic systems. This paper aims to study a possibility of creating well-conducting and durable elements in textile materials by combining two technologies – physical vapour deposition (PVD) and laser patterning. Design/methodology/approach: Thin conducting metallic layers on common fabrics do not provide satisfactory resistance to bending and stretching; therefore, selected textile composite materials have been proposed as a substrate. The conducting elements were produced in two stage process – deposition of thin metallic layer on textile composite and creating conducting elements by laser patterning. Laser ablation process was optimized using modelling in Comsol Multiphysics package. Properties of conducting structures were investigated experimentally and by modelling. Findings: This paper confirms the correctness of the choice of the textile composite as a substrate for conducting elements. The results have shown that combining PVD deposition of thin metallic layer and controlled laser ablation allow creating passive elements such as resistors, inductive coils and heaters. Computer simulations conducted in the Comsol Multihysics environment enabled to determine the temperature distribution around the heaters and to describe the dynamics of its changes. The obtained results allow to shorten time of the optimization process of structures with different geometry and assumed temperature distribution. Originality/value: The novelty of this research can be summarized as following: choosing of textile composites as substrates for conductive elements instead of textiles used so far in textronics; creating conductive structures on textile composites using combined technologies, PVD and laser patterning, for the first time; modelling of laser ablation process of thin metallic layer; and optimization of properties of conducting elements by computer modelling.